Rereading Bernard Etxepare’s Doctrina Christiana - Salaberri Muñoa, Patxi (EGAN, 2023)
The variegation of the edition in chained lines and without thematic differentiation of the Doctrina Christiana inscribed in the book Linguae Vasconum Primitiae (1545) by Bernard Etxepare presents objective difficulties for its correct comprehension. The present essay aims to establish the lines of coherence of the same and offers for this purpose a heterodox dissection of its various elements on the basis of both thematic and formal criteria.